The Problem of Responsible Parenthood in the Axiological Perspective Analysis Inspired by the Encyclical Humane Vitae - Wojewoda, Mariusz (Philosophy & canon law, 2019)
The article is devoted to the issue of responsible parenthood, which was formulated in the encyclical Humane Vitae by Paul VI in 1968. The content of the encyclical referred primarily to the issue of responsibility arising from fertilization. The author of the article relates the issue of parental responsibility to the care of a child with mild mental disability. Parental childcare is a consequence of calling the child to live. The author of the article analyses the issue of responsible parenting from the philosophical perspective and thus focuses on the recognition of the world of values by the parent-guardian of a person with intellectual disability. Close relationships with such a person require special spiritual, moral, and axiological sensitivity. The author of the article, in addition to the encyclical Humane Vitae, has been inspired by the reflections of Jean Vanier and Julia Kristeva on disability, resulting from two religious and secular perspectives.